Concurrent nephrotic syndrome and acute renal failure caused by chronic lymphocytic leukemia (CLL): a case report and literature review - Zhou Shufeng; Kang Kaifu; Liu Yongdong; Ju Yongle; Hu Haitang; Dou Xianrui; Chen Wenfang (BMC, 2011)
Abstract Kidney injury associated with lymphocytic leukemia (CLL) is typically caused by direct tumor infiltration which occasionally results in acute renal failure. Glomerular involvement presenting as proteinuria or even nephrotic syndrome is exceptionally rare. Here we report a case of 54-year-old male CLL patient with nephrotic syndrome and renal failure. The lymph node biopsy confirmed that the patients had CLL with remarkable immunoglobulin light chain amyloid deposition. The renal biopsy demonstrated the concurrence of AL amyloidosis and neoplastic infiltration. Combined treatment of fludarabine, cyclophosphamide and rituximab resulted in remission of CLL, as well as the renal disfunction and nephrotic syndrome, without recurrence during a 12-month follow-up. To our knowledge, this is the first case of CLL patient showing the nephrotic syndrome and acute renal failure caused by AL amyloidosis and neoplastic infiltration. Though AL amyloidosis caused by plasma cell dyscrasia usually responses poorly to chemotherapy, this patient exhibited a satisfactory clinical outcome due to successful inhibition of the production of amylodogenic light chains by combined chemotherapy.